Do Thai Medical Students Understand What Does 'AEC' Mean? A Cross-sectional Survey. - Jathurong Kittrakulrat; Ravipol Jurjai; Witthawin Jongjatuporn; Nicha Jarupanich; Annabel Bhamani; Krit Pongpirul (University Library System, University of Pittsburgh, 2018)
Background: Thai medical students are inevitably involved in the regional collaborative movement of 10 countries toward the ASEAN Economic Community (AEC), this study explored how well they understand the term. Methods: Twelve students proposed an abbreviation list, which was then rated for their difficulty level by another 55 students using a 5-point Likert scale. Three easy, three medium and three difficult abbreviations were randomly chosen and randomly listed in the final questionnaire, along with 'AEC'. Another randomly selected 60 students were asked to write the full term of the 10 abbreviations. Results: Of 34 abbreviations in the initial list, the selected terms were: CMCTSD, SRL, LSC, SOS, AM, LOL, WHO, USA, UK. They were correctly answered in 0, 0, 0, 6.67, 13.33, 46.67, 81.67, 96.67, and 98.33 percent, respectively. AEC was deemed moderately difficult, as 30% correctly expanded the abbreviation. Conclusion: Majority of medical students lacked an understanding of the current AEC movement.